Perceived health outcomes of recreation and happiness: exploring the mediating role of resilience - Sarol, Halil; Polat, Sezen Çimen; Ekinci, Erdoğan (Frontiers in Public Health, 2024)
Introduction Previous research has shown that leisure activities can positively influence perceived health outcomes by increasing individuals’ levels of physical activity. Yet, little has been discovered about the mechanisms that are driving this association. This study was conducted with the aim of examining the relationship between perceived health outcomes of recreation and happiness as well as the mediating effect of resilience. Methods The study comprised a total of 451 adult individuals residing in seven different geographical regions of Turkey, who were included using a convenience sampling method, and the data were collected between March and June 2023. Respondents completed assessments utilizing the Perceived Health Outcomes of Recreation, Brief Resilience Scale, and The Oxford Happiness Questionnaire-Short Form. Data analysis was executed employing the PROCESS macro for SPSS. Results The study’s findings revealed that perceived health outcomes of recreation had a positive effect on both happiness (β = 0.146, [95% CI: 0.106, 0.186]) and resilience (β = 0.156, [95% CI: 0.107, 0.205]). Resilience had a positive effect on happiness (β = 0.435, [95% CI: 0.362, 0.507]). Furthermore, the relationship between perceived health outcomes of recreation and happiness was partially mediated by resilience (β = 0.068, [95% CI: 0.042, 0.096]). Conclusion As a result, participating in leisure activities has been found to have a positive impact on perceived health outcomes, which in turn positively affects both happiness and resilience. Additionally, psychological resilience can be said to partially mediate the relationship between perceived health outcomes of recreation and happiness.